Prevalence and Tolerance of Prognostic Uncertainty Among Thoracic Oncologists. (30th April 2021) - Habib, Anand R.; Chen, Richard; Magnavita, Emily S.; Jaung, Tim; Awad, Mark M.; Odejide, Oreofe; Abel, Gregory A.
Abstract : : We undertook a cross-sectional survey of a random sample of thoracic oncologists from the American Society of Clinical Oncology clinical directory to characterize whether prognostic uncertainty has increased and if tolerance of uncertainty is associated with prognostic discussion practices. We also assessed the Physicians' Reactions to Uncertainty Scale and presented a vignette about an incurable patient with uncertain life expectancy. One hundred and ninety-two of 438 surveys (43.8%) were received. Of the respondents, 52.1% agreed "there is more prognostic uncertainty in the management of lung cancer now than 10 years ago, " and 37.4% noted difficulty "staying up-to-date." In multivariable analyses, physician-reported anxiety about uncertainty ( p = .05) and reluctance to disclose uncertainty ( p = .04) were inversely associated with reporting having prognostic discussions with most patients. For the vignette, 92.1% reported they would discuss incurability, but only 76.3% said they would discuss the patient's life expectancy. Our data suggest prognostic uncertainty has increased in thoracic oncology and oncologists' tolerance of uncertainty may affect discussion practices. Abstract : Limited tolerance of uncertainty may affect a clinician's communication practices and ability to assist patients with navigating such uncertainty. This article assesses the prevalence of prognostic uncertainty among thoracic oncologists, their personal tolerance of uncertainty, and whether their tolerance was associated with prognostic discussion practices.